1994
DOI: 10.1128/jvi.68.5.3051-3064.1994
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus contains cis-acting sequences that can suppress but not regulate origins of DNA replication

Abstract: Bovine papillomavirus (BPV) DNA has been reported to restrict its own replication and that of the lytic simian virus 40 (SV40) origin to one initiation event per molecule per S phase, which suggests BPV DNA replication as a model for cellular chromosome replication. Suppression of the SV40 origin required two cis-acting BPV sequences (NCOR-1 and-2) and one transacting BPV protein. The results presented in this paper confirm the presence of two NCOR sequences in the BPV genome that can suppress polyomavirus (Py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Either scenario would be consistent with previously described effects of HPV16 E1 on cell division and would likely be advantageous to vegetative papillomavirus DNA replication. Papillomavirus DNA replication occurs during S phase but is not limited to one occurrence per cellular replication cycle (36). Accordingly, a delay in cell cycle progression would allow greater opportunity for viral DNA replication.…”
Section: Figmentioning
confidence: 99%
“…Either scenario would be consistent with previously described effects of HPV16 E1 on cell division and would likely be advantageous to vegetative papillomavirus DNA replication. Papillomavirus DNA replication occurs during S phase but is not limited to one occurrence per cellular replication cycle (36). Accordingly, a delay in cell cycle progression would allow greater opportunity for viral DNA replication.…”
Section: Figmentioning
confidence: 99%
“…A similar, if not identical, set of cellular replication factors and enzymes, in addition to viral initiator proteins, is utilized by SV40 (Tsurimoto et al, 1990;Weinberg et al, 1990) and bovine papillomavirus-1 (Muller et al, 1994) at the origin of replication to initiate DNA synthesis. Analysis of the essential cis sequences shows that the BPV-1 minimal origin (MO) (Ustav et al, 1993) resembles a typical eukaryotic origin of replication (DePamphilis, 1993) and it has been suggested that this similarity could also be extended to the mechanisms of replication of all papovaviruses (Nallaseth and DePamphilis, 1994;Bonne-Andrea et al, 1995). However, the ability of the papillomaviruses to be stably maintained as plasmids distinguishes them from other papovaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the multiple replication intermediates detected in the present study may be ascribed to that BPV-1 has different replication modes in S. cerevisiae . Two replication modes: an ordered once-per-S-phase fashion and a random fashion have been reported for the replication of BPV-1 DNA in eukaryotic cells (Berg et al 1986 ; Gilbert and Cohen 1987 ; Nallaseth and DePamphilis 1994 ; Ravnan et al 1992 ).…”
Section: Discussionmentioning
confidence: 99%